The regulation of fecal microbiota for transplantation: An international perspective for policy and public health. (3rd July 2015) - Edelstein, Carolyn A.; Kassam, Zain; Daw, Jamie; Smith, Mark B.; Kelly, Colleen R.
Abstract: Clostridium difficile is the most common hospital-acquired pathogen in the US, and recurrent C. difficile infection (CDI) is a major public health issue. Twenty per cent of CDI patients experience recurrence, and their risk of recurrence rises with each failure to achieve clinical resolution. Fecal microbiota transplantation (FMT) is a remarkably efficacious treatment for recurrent CDI. However, national health agencies are grappling with the appropriate regulatory paradigm to apply to this innovative treatment. Current FMT regulations in the US, Canada, Western Europe, Australia, and China are in varying degrees of flux, although many regulators are choosing to apply the drug and biologic framework. FMT regulations should allow recurrent CDI patients safe access to this treatment as research continues. Regulating FMT like a drug or biologic, although most convenient from a legal perspective, overly restricts access while under-regulating the methods by which the stool is screened, processed, stored, and used. Human tissue and tissue-based products regulations could achieve the desired level and kind of oversight, but fecal microbiota for transplantation fail to meet applicable statutory definitions. A custom regulatory solution would be more appropriate, but many pathways that regulators may take to achieve this goal require time and resources for health agencies to develop.